EFFECTS OF MENTAL FATIGUE ON VISUAL SCANNING SPEED IN FIRST-PERSON SHOOTER ESPORTS ATHLETES - Kurniawan, Tian (ASEAN Journal of Sport for Development and Peace, 2022)
Esports competitions in Indonesia have become increasingly popular, various prestigious tournaments both on the national and international levels have increased competition among athletes. Cognitive ability has a big enough role in the success of an esports athlete, so the fatigue factor that can reduce this ability needs to be considered. The purpose of this study was to identify whether the effects of mental fatigue can reduce the speed of athletes in visual scanning in esports athletes, especially athletes in the first-person shooter genre. Forty UPI esports athletes voluntarily carried out this research, ten each from Valorant, CS-GO, Overwatch and, Point Blank. In the first session 20 people will do a Visual Scanning Speed test after being given mental fatigue intervention and 20 people will take a Visual Scanning Speed test after watching TV as a control group, and they will switch groups in the next session. The data shows that mental fatigue in the experimental group significantly reduces the ability of Visual Scanning Speed. The results show that mental fatigue can significantly reduce cognitive performance, so the mental state of esports athletes needs to be considered to optimize their performance.